1977
DOI: 10.2135/cropsci1977.0011183x001700020004x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Diallel Crosses and Second Generation Synthetics of Alfalfa Derived from Partly Inbred Parents. II. Earlines and Mortality1

Abstract: In an alfalfa (Medicago sativa L.) breeding study conducted under conditions of high competition between plants, combining ability for earliness and mortality was evaluated from diallel crosses among selected parents, which had been partly inbred by selfing. The performance of first and second generation synthetics was also studied. For both earliness and mortality (percentage of blooming or dead plants, respectively), general combining ability (GCA) was considerably larger than specific combining ability (SCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The only comparison of selfing generations for synthetic varieties of forage crops that has encompassed as many generations as the present study (from S 0 through to S 4 ) was reported by Rotili (1976) for forage yield of alfalfa. As a function of selfing generation, a curvilinear pattern of response also emerged in this study of Rotili (1976), which featured a plateau in the S 2 generation. Later on, Rotili et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The only comparison of selfing generations for synthetic varieties of forage crops that has encompassed as many generations as the present study (from S 0 through to S 4 ) was reported by Rotili (1976) for forage yield of alfalfa. As a function of selfing generation, a curvilinear pattern of response also emerged in this study of Rotili (1976), which featured a plateau in the S 2 generation. Later on, Rotili et al.…”
Section: Discussionmentioning
confidence: 94%
“…Studies of forage crops have not provided definite evidence for the usefulness of inbreeding in selection schemes (e.g. Rotili 1976, Berdhal and Ray 2004). In berseem populations, self‐fertility decreases dramatically with increased inbreeding, although many plants with high self‐fertility can be located within populations (Iannucci 2001a).…”
mentioning
confidence: 99%